2007
DOI: 10.1073/pnas.0707210104
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression patterns of human colon tops and basal crypts and BMP antagonists as intestinal stem cell niche factors

Abstract: Human colonic epithelial cell renewal, proliferation, and differentiation are stringently controlled by numerous regulatory pathways. To identify genetic programs of human colonic epithelial cell differentiation in vivo as well as candidate marker genes that define colonic epithelial stem/progenitor cells and the stem cell niche, we applied gene expression analysis of normal human colon tops and basal crypts by using expression microarrays with 30,000 genes. Nine hundred and sixty-nine cDNA clones were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
488
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(527 citation statements)
references
References 31 publications
25
488
0
2
Order By: Relevance
“…88,89 Human intestinal epithelia contain mRNA transcripts for the majority of Eph receptor and ephrin family members and a few of these have been directly implicated in intestinal epithelial homeostasis. 90,91 The general expression pattern of Eph receptors and ephrins is relatively similar in the mucosal epithelium of the small and large intestines. 90 In particular, EphB2 and EphB3 expression is concentrated in the cells that populate the crypt nadirs and decreases toward the top of the villi.…”
Section: Eph Receptors and Ephrins In Gut Epitheliummentioning
confidence: 99%
“…88,89 Human intestinal epithelia contain mRNA transcripts for the majority of Eph receptor and ephrin family members and a few of these have been directly implicated in intestinal epithelial homeostasis. 90,91 The general expression pattern of Eph receptors and ephrins is relatively similar in the mucosal epithelium of the small and large intestines. 90 In particular, EphB2 and EphB3 expression is concentrated in the cells that populate the crypt nadirs and decreases toward the top of the villi.…”
Section: Eph Receptors and Ephrins In Gut Epitheliummentioning
confidence: 99%
“…Moving upwards along the crypt-to-villus axis, terminal differentiation coincides with the more restricted membrane-bound b-catenin localisation and its absence in the nucleus and cytosol (Figure 1). Recently, it has been reported that the BMP antagonists, gremlin 1, gremlin 2, and chrodin-like 1, are selectively expressed by crypt-based myofibroblasts and smooth muscle cells (Kosinski et al, 2007). Moreover, Gremlin 1 was shown to activate Wnt/b-catenin signalling in normal rat intestinal epithelial cells, thus indicating that stromal-derived factors regulate Wnt/b-catenin-signalling activity in the intestinal stem cell niche.…”
mentioning
confidence: 99%
“…44 EphA2 and its ligand Ephrin A1 (previously referred to as B61 and the primary endogenous ligand for EphA2) also have been reported to act in an autocrine loop to regulate intestinal cell migration and barrier function. 45,46 In intestinal neoplasia, EphA2 has been reported to be up-regulated in human colorectal cancers, and EPHA2 overexpression correlates with colon cancer metastasis and high microvessel count in primary human colorectal cancers.…”
mentioning
confidence: 99%